MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP PADA MATERI HIMPUNAN MENGGUNAKAN PENDEKATAN SAINTIFIK DENGAN SETTING MODEL KOOPERATIF TIPE JIGSAW - Neng Cucu Nurmaenah; Selvia Agina; M. Afrilianto; Ratna Sariningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This type of research is a classroom action research which aims to determine the improvement of students' mathematical learning outcomes after using scientific learning with the jigsaw cooperative model setting on the subject matter of the set. This research was carried out at SMPN 3 Cihampelas in the 2019/2020 school year with the object of research in class VII totaling 36 students. This research was conducted in 2 cycles. Each cycle consisted of 2 meetings, the number of meetings in this classroom action research was 6 meetings, the first meeting was used for the pretest, 2-3 meetings were used for the first cycle of learning, 4-5 meetings were used for learning cycle 2, and the second meeting was 6 carry out posttest to review student learning outcomes. The instruments used in data collection were the pretest and posttest questions and observations. The data analysis technique used descriptive statistics in the form of averages and percentages. Researchers act as the implementation of learning and mathematics teachers as observators in class VII SMPN 3 Cihampelas. The results showed that: (1) There was an increase in student learning outcomes as indicated by an increase in the first cycle with an average value of 60.05 with a percentage of 44.4% and in the second cycle the average value achieved was 84.67 with a percentage of 83.3 %; (2) The activities of teachers and students in learning are good enough in each cycle, but there are still deficiencies that cannot be fixed, namely student activeness in the learning process.